Working for the Government: A Logit Regression Analysis - Woo, Kuan Heong (2016)
In a fast-paced, dynamic and ever-challenging era, when most job seekers looking for a job which could offer them with large salary, advancement opportunities and career fulfilment, the stereotypical view of government jobs deem dull and old fashioned making it more important than ever to understand what attract job seekers to the public service. University and college graduates will be a significant of public service renewal. Using a sample of 519 graduating students from two private higher education institutions in Malaysia, this study investigates factors that affect graduating students in seeking government jobs. Logistic regression is used to analyze the data collected through a cross-sectional survey. Results indicate that the perceived attractiveness of public employment (Attrctv, the index of public employment attractiveness), race (Race), proficiency in Malay and English languages (MalayPro and EnglishPro) are statistically significant in affecting the likelihood of Malaysian graduating students in choosing government jobs, ceteris paribus. Based on these findings, several implications are noted to policy makers and public personnel managers so that they have better understanding on factors affecting graduating students in considering sectoral employment and to guide remedial action.